Peran Prolanis Memberikan Perlindungan Biaya Kesehatan Mencegah Pengeluaran Katastropik di Kota Jambi - Adila Solida; Arnild Augina Mekarisce; Evy Wisudariani (Universitas Batanghari Jambi, 2023)
The increasing incidence of catastrophic diseases such as hypertension and diabetes mellitus has an impact on catastrophic expenditure in Jambi City. Very high health costs risk causing household economic fragility. Prolanis is one of the programs organized by BPJS Health as part of the National Health Insurance to manage participants' chronic diseases by optimizing efficient health costs. This study aims to analyze costs due to illness and the role of Prolanis in providing health cost protection to participant households so as to prevent catastrophic expenditures. The research approach is quantitative and qualitative which describes the components of direct costs, indirect costs and total costs due to diabetes mellitus and hypertension and assesses the role of Prolanis in preventing catastrophic events in the household. Respondents totaling 180 people were selected using purposive sampling technique. The informants consisted of 20 Prolanis participants who regularly took part in Prolanis activities. The research was conducted in five work areas of community health centers in Jambi City. Quantitative data was analyzed using statistical software through descriptive statistical analysis stages. Qualitative data is summarized in an interview results matrix based on content. The results obtained were that the total costs borne by Prolanis participants due to hypertension and diabetes mellitus had decreased significantly while participating in Prolanis activities. The role of Prolanis for participants is to prevent complications from the disease they are suffering from, regulate the use of medication wisely, receive coordinated and routine disease treatment, and change to a healthier lifestyle. The role of Prolanis felt by participants has an impact on health expenses which can be reduced so that participants are free from catastrophic expenses. It is recommended that the Community Health Center as the technical implementing unit for Prolanis activities expand the scope of Prolanis participation in the work area and increase awareness of people suffering from chronic diseases to actively participate in Prolanis activities to prevent families from experiencing catastrophic spending.